Clinical and Economic Burden of Patients with Chronic Hepatitis C with Versus Without Antiviral Treatment in Japan: An Observational Cohort Study Using Hospital Claims Data - Yamazaki, Kiyotaka (Infect Dis Ther, 2019)
INTRODUCTION: Japan has one of the highest prevalence rate of chronic hepatitis C (CHC) in the industrialized world. However, the burden of CHC treatment is poorly understood. Thus, the healthcare resource utilization and costs of treated versus untreated patients, and patients with early versus delayed treatment initiation, were assessed in Japan. METHODS: Adult patients with ≥ 2 CHC diagnoses were identified from the Medical Data Vision hospital claims database (1 April 2008–31 May 2016). The presence or absence of antiviral treatment claims was used to form the treated and untreated cohorts, respectively. Among treated patients, the presence of a cirrhosis-related diagnosis was used as an indicator of delayed treatment. The index date was defined as the date of the first antiviral claim for treated patients and randomized to any date with a medical visit for untreated patients. Annualized total healthcare costs and costs associated with hepatic manifestations (HMs) or extrahepatic manifestations (EHMs) were evaluated from the index date to the last observed medical visit. RESULTS: Of 100,125 patients with CHC, 12,984 were treated (early: 8104, delayed: 4880) and 87,141 were untreated. After adjusting for covariates, untreated patients had ¥613,034 ($5456 USD; ¥1 = $0.0089) higher annual medical costs compared with treated patients (P < 0.001), a difference driven by higher inpatient costs. Between 65% (treated patients) and 70% (untreated patients) of medical costs were EHM-related and between 14% (untreated patients) and 15% (treated patients) were HM-related. Patients in the delayed treatment cohort had ¥114,347 ($1018) higher annual medical costs (P < 0.001) versus those in the early treatment cohort. About 95% of these costs were EHM-related, and 64% were HM-related. CONCLUSION: Withholding or delaying antiviral treatment initiation for Japanese patients with CHC increases the clinical and economic burden associated with HMs and EHMs. FUNDING: AbbVie.